Sorption of phenol from aqueous solutions using acid-treated rice husk - Daffalla, S.B. (WITPress, 2013)
In this study, the development of low-cost adsorbent material from cheap abundant rice husk was developed via sulfuric acid treatment. The physiochemical properties and functional groups characterization of the adsorbents were evaluated. The effects of pH and contact time were studied in batch experiments. It was found that sulfuric acid treatment affects the pore size distribution, surface area, morphological structure and functional groups of the rice husk. Analysis showed that the surface area of rice husk was increased 7 times from 7.14 to 50.17 m2.g-1. In addition, the surface structure of the rice husk was changed from a non-porous to a porous surface after treatment. On the other hand, the uptake of phenol onto the rice husk was increased from 20.06 to 48.62 after treatment. Further, the percentage adsorption of phenol increased with the increase of the contact time. The maximum uptake of phenol can be obtained at pH 4. The equilibrium data were well described by the Freundlich model, while the kinetic data were well fitted to the models of pseudo second order and Elovich, and followed closely by the Elovich chemisorption model. Â© 2013 WIT Press.